1998
DOI: 10.1111/j.1528-1157.1998.tb01434.x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Temporal Hypometabolism in Epilepsy

Abstract: Summary: Purpose: Positron emission tomography (PET) has proven useful in epilepsy surgery for its ability to identify unilateral temporal hypometabolism (UTH), which is predictive of good surgical outcome. The significance of bilateral temporal hypometabolism (BTH) is not known.Methods: We identified all patients who had marked bilateral reduction in temporal lobe metabolism relative to the cerebellar hemispheres and compared their clinical features and treatment outcomes with those of control patients with U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 26 publications
6
37
1
Order By: Relevance
“…The authors reviewed work on neuronal grafting for the treatment of hippocampal lesions and epilepsy, and they concluded that embryonic neurons might provide significant clinical benefits. A similar conclusion was previously reached by other authors (1,8). Although some authors demonstrated that xenotransplanted human fetal brain cells were capable of surviving in ischemic areas for 1 week (1), I have doubts regarding the effectiveness of transplantation for the treatment of cerebrovascular sequelae and epileptogenic zones.…”
Section: Clinical Prospects For Neural Grafting Therapy For Hippocampsupporting
confidence: 64%
See 1 more Smart Citation
“…The authors reviewed work on neuronal grafting for the treatment of hippocampal lesions and epilepsy, and they concluded that embryonic neurons might provide significant clinical benefits. A similar conclusion was previously reached by other authors (1,8). Although some authors demonstrated that xenotransplanted human fetal brain cells were capable of surviving in ischemic areas for 1 week (1), I have doubts regarding the effectiveness of transplantation for the treatment of cerebrovascular sequelae and epileptogenic zones.…”
Section: Clinical Prospects For Neural Grafting Therapy For Hippocampsupporting
confidence: 64%
“…We recently evaluated the flow dynamics of degenerative spinal disease with perfusion-weighted magnetic resonance imaging (1). In that study, perfusion parameters were analyzed with principles of echo-shifting with a train of observations sequences for six patients with CSM.…”
mentioning
confidence: 99%
“…In symptomatic cases, positron emission tomography (PET) documented interictal hypometabolic alterations linked to the epileptogenic region, and the area associated with these alterations far exceeded the boundaries of the epileptogenic lesion. Usually these changes are ipsilateral (42,43), but patients with bilateral temporal hypometabolism have a higher frequency of generalized seizures and a poorer outcome (44). Moreover, proton magnetic resonance spectroscopy revealed that a bilateral reduction in the concentration of N-acetyl-aspartate can exist in many patients with focal epilepsies.…”
Section: Discussionmentioning
confidence: 99%
“…The high incidence of bilateral epileptiform abnormalities in our group of patients supports the view that the TLE is commonly a bilateral disease even though a unilateral focus is likely to predominate in the great majority of cases (5-7,9-11). Bilateral abnormalities have also been revealed by neuropathologic, volumetric MRI and proton magnetic resonance spectroscopy (MRS) studies (1,6,9,(20)(21)(22)(23)(24). Bilateral structural or pathologic disease is certainly a sufficient cause for bilateral epileptiform abnormalities in the EEG.…”
Section: Discussionmentioning
confidence: 99%